Risk factors for pregnancy-related pelvic girdle pain: a scoping review - Francesca Wuytack; Cecily Begley; Deirdre Daly (BMC, 2020)
Abstract Background Pregnancy-related Pelvic Girdle Pain (PPGP) is a common complaint. The aetiology remains unclear and reports on risk factors for PPGP provide conflicting accounts. The aim of this scoping review was to map the body of literature on risk factors for experiencing PPGP. Methods We searched the databases PubMed, Embase, CINAHL, PsycINFO, MIDIRS, and ClinicalTrial.gov (3 August 2020). We selected studies with two reviewers independently. Observational studies assessing risk factors for PPGP were included. Studies examining specific diagnostic tests or interventions were excluded. Results We identified 5090 records from databases and 1077 from ClinicalTrial.gov. Twenty-four records met the inclusion criteria. A total of 148 factors were examined of which only 14 factors were examined in more than one study. Factors that were positively associated with PPGP included a history of low back or pelvic girdle pain, being overweight/obese, already having a child, younger age, lower educational level, no pre-pregnancy exercise, physically demanding work, previous back trauma/disease, progestin-intrauterine device use, stress, depression and anxiety. Conclusions A large number of factors have been examined as potential risk factors for PPGP, but there is a lack of repetition to be able to draw stronger conclusions and pool studies in systematic reviews. Factors that have been examined in more than five studies include age, body mass index, parity and smoking. We suggest a systematic review be conducted to assess the role of these factors further in the development of PPGP.